PENGAWASAN TERHADAP BIRO PERJALANAN WISATA ONLINE YANG TIDAK MEMILIKI IZIN DI PROVINSI BALI - Ni Putu Ayu Arsani; Cok Istri Anom Pemayun; Ni Gusti Ayu Dyah Satyawati (Kertha Negara : Journal Ilmu Hukum, 2013)
Travel agency is a business trip planning and tourism services. Theincreasing of knowledge in the field of technology it is now make many travel agienciesare using online media to conduct the transaction.. Therefore, it is need a supervisionby the government against the Travel agency. This paper discuss the issues concerningthe government oversight of online Travel agency that does not have a license tooperate and remedies that can be taken when fraud or breach of contract occurred. Thispaper using an empirical legal research. The conclusion of this paper are first, thesupervision facing difficulty because of the limitation of the number of the supervisingteam and the regulation concerning online travel agencies are unclear, which arecause the growth number of the illegal online travel agencies. Second, remedies thatcan be taken against fraud and breach of contract in an online Travel Agency that doesnot have a license to operate in the province of Bali.